2007
DOI: 10.1158/1078-0432.ccr-06-1772
|View full text |Cite
|
Sign up to set email alerts
|

Standard Treatments Induce Antigen-Specific Immune Responses in Prostate Cancer

Abstract: Purpose: Prostate tumors express antigens that are recognized by the immune system in a significant proportion of patients; however, little is known about the effect of standard treatments on tumor-specific immunity. Radiation therapy induces expression of inflammatory and immunestimulatory molecules, and neoadjuvant hormone therapy causes prominent T-cell infiltration of prostate tumors. We therefore hypothesized that radiation therapy and hormone therapy may initiate tumor-specific immune responses. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 65 publications
12
142
0
2
Order By: Relevance
“…Ab responses against autoantigens were identified by SEREX in nonmetastatic PCa patients undergoing standard RT or brachytherapy (34). New autoantibody responses were observed in 14% of patients after RT and in 20% of patients after brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ab responses against autoantigens were identified by SEREX in nonmetastatic PCa patients undergoing standard RT or brachytherapy (34). New autoantibody responses were observed in 14% of patients after RT and in 20% of patients after brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen ablation in prostate cancer patients may activate immune responses to some prostate tumor antigens by increasing the pool of naive T cells (as demonstrated by TCR rearrangement excision circle [TREC] analyses; TRECs are stable DNA circles excised from T cell germline DNA to allow for TCR formation during early T cell development and exist in high concentrations in thymic emigrants), decreasing and/or diluting the population of Tregs, and favoring the concomitant infiltration of T cells into tumor beds (36,37). One study performed on 73 men bearing nonmetastatic prostate cancer and 50 controls showed that neoadjuvant hormonal and radiation therapy (but not radical prostatectomy) can elicit a tumor-specific autoantibody response (38). Humoral responses arose early and were durable in most cases, prompting the manipulation of B cell responses by immunotherapy.…”
Section: Immunostimulatory Side Effects Of Anticancer Drugsmentioning
confidence: 99%
“…A wide variety of tumor Ags are recognized, including overexpressed proteins (e.g., HER-2/neu), aberrantly expressed proteins (e.g., cancertestis Ags), and a plethora of apparently normal self-proteins (41,42). Furthermore, standard treatments for cancer, such as hormone and radiation therapy, can trigger additional autoantibody responses, presumably through presentation of dying tumor cells to the immune system (43).…”
Section: B Cells In Cancermentioning
confidence: 99%